DIPLYCOSIA MEKONGGAENSIS (ERICACEAE, GAULTHERIEAE), A NEW SPECIES FROM SULAWESI, INDONESIA - Argent, G.; Widjaja, E. A. (Edinburgh Journal of Botany, 2015)
Diplycosia mekonggaensis Argent & Widjaja (Ericaceae, Gaultherieae) is described and illustrated as a new species from the island of Sulawesi in Indonesia. Diagnostic characters are given and comparisons with related species are made.
Keywords: Diplycosia; Ericaceae; Gaultherieae; Indonesia; new species; Sulawesi